Experimental study on the effectiveness of sterilizing pouch, bond paper, dental bib and cheesecloth in instrument box in preventing contamination of mouth mirrors within a 24-hour period - Guzman, Ernest Joie T.; Ritua, Marc Kenneth S.; Malenab, Virgilio, Jr.; De Castro, Elizabeth G.
Sterilization involves use of different packaging systems to ensure prolonged sterility of instruments. These include materials such as dental bib, cheesecloth, bond paper, and sterilizing pouches. The research attempts to identify which of these packaging systems prevents recontamination after sterilization within a 24 hour storage period.
The study included 50 front surface mirrors divided into 5 groups; 10 mouth mirrors wrapped in paper, 10 in dental bib, 10 in cheesecloth, 10 in sterilizing pouches and 10 instruments which are unwrapped. All mouth mirrors underwent mechanical cleaning with soap and air dried. The study used autoclaving at 121°C for 15 minutes at 15 psi. After sterilization, the mouth mirrors were stored for 24 hours in a container boxinside the sterilizing room. The sterilized mouth mirrors were swabbed and incubated for an hour in Brain-Heart Infusion broth and streaked in Blood Agar plate then incubated for 24 and 48 hours. Occular examination of the Blood Agar plates was done after incubation for identification of presence microorganisms. Turbidity test of the Brain-Heart infusion broth was used to confirm presence of microorganism.
1 out of 50 samples had positive microbial contamination which was exhibited by presence of microorganism in the Blood Agar plate after incubation. Turbidity test showed negative results in all samples. The result was analyzed using the Z-test proportions. Statistical analysis showed no significant difference between all groups in maintaining sterility after a 24 hour period.
Results showed no significant difference in the effectiveness in preventing recontamination between all groups after 24 hours.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Sterilizing packaging system; Recontamination; Sterility; Infection Control; Sterilization; Periodontal diseases